Rationalization of supramolecular interactions of a newly synthesized binuclear Cu(II) complex derived from 4,4′,6,6′-tetramethyl 2,2′-bipyrimidine ligand through Hirshfeld surface analysis - Pramanik, Samit; Mukhopadhyay, Subrata; Das, Kinsuk (European Journal of Chemistry, 2022)
A new binuclear copper (II) complex [Cu2L2Cl4(H2O)2] (1) derived from 4,4',6,6'-tetramethyl-2,2'-bipyrimidine (L) has been synthesized and characterized by the single crystal X-ray diffraction method. Single crystal analysis of complex 1 reveals that it crystallizes in the space group P21/n under a monoclinic system (β = 97.995(2)°, a = 7.6483(2), b = 7.2158(3) and c = 17.8477(6) Å). The ligand acts as a bis-bidentate one and each copper (II) center bears a square pyramidal geometry exploiting N2Cl2O chromophore. In the solid state, the complex is stabilized through classical O-H···Cl intermolecular hydrogen bonding incorporating coordinated water (as a solvent) and chloride ions and lone pair···π interactions. The Hirshfeld surface analysis demonstrates H···H/H···H, H···Cl/Cl···H, H···C/C···H, and C···Cl/Cl···C intermolecular interactions as the major contributor interactions in the solid-state packing of the molecular crystal. Interaction energy calculations carried out employing the wavefunction generated via B3LYP/6-31G(d,p) highlight the dominance of electrostatic energy and the contribution of polarization and dispersion energy towards the total energy of complex 1 in the solid state.